Fast 3D modelling and precise measurement of soft tissue for craniofacial reconstruction using laser scanning - Ibrahim, Mohd. Sharuddin; Setan, Halim; Majid, Zulkepli (2005)
This multi-disciplinary research (between UTM, SIRIM and USM) focuses on medical (i.e. craniofacial) applications. Various imaging sensors/techniques are used to capture the craniofacial data (i.e. soft and hard tissues) of real patients at HUSM, Kubang Kerian, Kelantan. Soft tissue data are obtained from laser scanning (using VIVID910) and photogrammetry techniques, while hard tissue data are captured via CT scan, X-Ray and MRI. This paper describes the configuration, data capture, processing, and analysis of soft tissue data obtained from laser scanning system. The laser scan data of human faces are processed (using RAPIDFORM) to generate 3 dimensional (3D) computer model and landmarks measurement. The results show that the system is capable of producing fast 3D computer model and high precision (i.e. sub-mm level) measurement of the craniofacial.